Aid, catastrophes and the Samaritan's Dilemma - Paul A. Raschky; Manijeh Schwindt (University of Innsbruck, Department of Public Finance, 2008)
This paper discusses the impact of foreign aid on the recipient country's preparedness against natural disasters. The theoretical model shows that foreign aid can have two opposing effects on a country's level of mitigating activities. In order to test the theoretical propositions we analyse the effect of foreign aid dependence on exante riskmanagement activity proxied by the death toll from major storms, floods and earthquakes occurring worldwide between 1980 and 2002. We find evidence that the crowding-out effect of foreign aid outweighs the preventive effect in the case of storms, while there is mixed evidence in the case of floods and earthquakes.
Keywords: O17; O19; Q54; 330; foreign aid; Samaritan's Dilemma; natural hazards; Entwicklungshilfe; Naturkatastrophe; Katastrophenhilfe